Vote Invalidation sebagai Manipulasi Elektoral dalam Pemilu Legislatif 2024 di Desa Mentengsari, Kabupaten Cianjur - Aldian Farobby; Mohammad Azmi; Shafira Tricantika; Sandrina Malakiano (Politeia: Jurnal Ilmu Politik, 2026)
Local-level elections are crucial for assessing substantive democratic quality but are highly vulnerable to subtle forms of electoral manipulation. This article examines vote invalidation in the 2024 Legislative Election in Mentengsari Village, Cianjur Regency, focusing on the deliberate nullification of valid votes through ballot re-marking. Using a qualitative case study based on secondary data from decisions of the Constitutional Court, Cianjur District Court, and the Election Organizers Ethics Council, the study reveals that manipulation occurred not through vote inflation, but through the destruction of legally cast votes. This strategy proved low-risk and effective in closely contested local elections. The article argues that safeguarding local electoral integrity requires stronger preventive oversight mechanisms to protect valid votes from non-conventional manipulation.